Religious Redemption as the Motivation for the Jihadist Crime-Terrorism Nexus: A Critical Inquiry - Karimi, Nima (Terrorism and political violence, 2025)
In their influential article on the “crime-terror nexus” Basra and Neumann state that “jihadism can affect a criminal’s radicalisation process in two ways: it can offer redemption from past sins, or it can legitimise crime.” During their analysis, though, the two interpretive options become in effect one, reflecting the dominant orientation to the continuity of criminality and terrorism (religious or otherwise) as social phenomena. Examining the work of Basra and Neumann, and others addressing the issue, this article argues for a crucial aspect of discontinuity between some jihadists’ terrorist commitments and their criminal pasts. The redemptive motivation for turning from criminality to jihadism warrants being analyzed more fully and carefully to better explain why only a handful of individuals with a criminal background become jihadists. Crucially, for example, and contrary to a prevailing narrative in the literature, jihadists appear to prioritize seeking redemption for their sins, as defined by their religion, rather than for crimes, as delineated by secular society. Fully recognizing and investigating the “definition of the situation” that Western Muslim criminals and jihadist recruiters share is essential to understanding the motivations for the nexus in many instances, and thus grasping how best to counter it.